Primary Fallopian Tube Carcinoma (PFTC), A Rare Malignancy of Female Genital Tract (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Background: Primary fallopian tube carcinoma (PFTC) is one of the rarest malignancies of female genital tract. It represents